2016
DOI: 10.1051/matecconf/20164002008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Value Engineering to Rework Reduction in Ship Building Project

Abstract: Abstract-Value engineering is an organized creative technique to analyze the function of a product or a system for achieving the required function at minimum cost along with required performance, reliability, maintainability, appearance, safety etc. Value engineering has been proved to be a very effective tool of materials management and cost reduction in modern industry. It proceeds with the analysis of the value or the utility of the product and then to investigate as to how the value can be improved or if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Tang and Bittner [29] developed a creative design solution for a marine construction project. The VE's concept has also been applied in ship hull construction by [30] on reducing the rework in the shipbuilding project using matrix and costbenefit function through the VE workshop. Karami and Olatunji [31] suggested that the marine project's key protocols should be applied to reduce cost and time while optimising the project's quality.…”
Section: 2mentioning
confidence: 99%
“…Tang and Bittner [29] developed a creative design solution for a marine construction project. The VE's concept has also been applied in ship hull construction by [30] on reducing the rework in the shipbuilding project using matrix and costbenefit function through the VE workshop. Karami and Olatunji [31] suggested that the marine project's key protocols should be applied to reduce cost and time while optimising the project's quality.…”
Section: 2mentioning
confidence: 99%
“…Currently, there are about 3,250degree level technical institutions in India with a total intake of about 15,50,000 students admitted every year. There are more numbers of technical institutions established in southern India and the growth rate of technical institutions in the recent years has been extraordinary and the problems related to this expansion are also steep [31][32][33][34][35]. This unique growth in engineering education has been caused by policy changes to permit to start self financing engineering institutions.…”
Section: Literature Reviewmentioning
confidence: 99%